Teste de progênies de Ilex paraguariensis A.St.-Hil em plantio puro no sudoeste do Paraná - Amaral, Italo Mayke Gonçalves (2018)
Ilex paraguariensis A. St.-Hil. is a forest species of great economic importance to the southern States of Brazil, considering the historical and cultural formation of the region as it is raw material in the production of yerba mate, the main ingredient of typical drink mate. Even so, many production bottlenecks still remain to be resolved, such as involving the focus of this study, in order to bring the productive chain of the culture to a profitable, socially fair and environmentally correct. With the study, the objective of measuring the progress of different progenies of species in a homogeneous planting in full sun were tested 18 progenies in experimental design of randomized blocks, with 4 blocks and 5 plants each progeny per block. The variables evaluated in each plant were lap height, diameter, number of leaves, leaf area, projection area, chlorophyll content, total sugar and protein, obtaining later increments, relative growth and correlation with your mood. The results showed the best medium to increase in diameter of the neck to the progenies, 3-QUE, 5-QUE and 12-IVA increase in height, 3-QUE, 5-QUE and 8-CAS, increment in area 2-CAS, 17-DES, and 4-DES, relative growth (%) in diameter, 9-BAR, 1-BAR and 13- CAS, in alture 3-QUE, 8-CAS and 5-QUE, and for height and diameter of the Cup ratio (h/d) the progenies, 16-DES, 3-QUE and 18-DES. As for the number of sheets the progeny 3-QUE obtained highest average with the highest increase over the 14 months. As the chlorophyll a progeny 8-CAS obtained greater ICF, to the protein and total sugar, the averages were classified into 3 groups, and for the average leaf area per sheet to 16 months the progeny 5-QUE obtained greater value. Among the correlation, there was significance among the variables of time with temperature, humidity and precipitation, temperature neck diameter, number of sheets with temperature and precipitation with Cup area. After achieving the ranking of the progenies based on dataset, the progenies 5-QUE, 3-QUE, 2- CAS and 8-CAS, showed better development for the municipality of Dois Vizinhos-PR. On genetic divergence, by multivariate analysis were obtained four principal component groups, whose first component represented 24.768% of the variance, and loads the main variables of the analysis, the highest correlations, the increment in Height, the Increase in diameter of the neck, the relative growth in number of leaves and leaf area, the second component, which loads the variables relative growth in the area of copa and chlorophyll content, explains 17.381% of the variance, the third component loads the variable height and Diameter of the neck and 17.374% of variance explained, and the fourth component, loads the content of protein and sugar content and represents 17.102% of the variance. It is concluded that the progenies 3-QUE and 5-QUE has higher performance in the production of leaves and climatic variables correlate differently among the progenies, morphological variables increase in height and in diameter of the neck and relative growth in number of leaves were the main variables to characterize the growth, by the hierarchical method of Ward were obtained five groups of Progenies, being the Group 3 more suitable for cultivation in the municipality of Dois Vizinhos and the region.